Aplikasi Kegiatan pada Unit Kegiatan Mahasiswa LP3I Computer Club (UKM LCC) - Rendi Adriandi; Ummu Radiyah; Anton Anton; Esron Rikardo Nainggolan (INFORMAL: Informatics Journal, 2020)
The development of telecommunications technology is very rapid along with the times that have reached the era of "technology in the grip". The use and utilization of information technology in this grip is needed by LCC UKM or LP3I Computer Club Student Activity Unit, where this UKM regularly holds training activities or seminars both for participants from internal campus and outside campus. But apparently the data management of participants who attended the activity was still manual, namely still using paper to record attendance of participants so there was no database of participants which caused the committee to find it difficult to contact participants who had already participated in UKM LCC activities if there were new activities. The main objective of the research is to produce an application based on Android activities to facilitate the committee in creating a participant database. The making of this application uses the scrum method so that it can make priorities in building this application as needed. The results of this study, the LCC UKM committee no longer needs to use paper for recording attendance and the participant database can be stored directly on the server.